Financial sector development in the Pacific Rim - Itō, Takatoshi, 1950-; Rose, Andrew, 1959- (NBER-East Asia Seminar on Economics (Series), 2009)
Examines the institutional factors influencing financial innovation, the consequences of financial development, widespread consolidation occurring through mergers and acquisitions, and the implementation of policy reform.--From publisher description.